Aberrant human ClpP activation disturbs mitochondrial proteome homeostasis to suppress pancreatic ductal adenocarcinoma. Issue 9 (15th September 2022) - Wang, Pengyu; Zhang, Tao; Wang, Xinjing; Xiao, Hongying; Li, Huiti; Zhou, Lin-Lin; Yang, Teng; Wei, Bingyan; Zhu, Zeyun; Zhou, Lu; Yang, Song; Lu, Xiongxiong; et al.
Summary: The mitochondrial caseinolytic protease P (ClpP) is a target candidate for treating leukemia; however, the effects of ClpP modulation on solid tumors have not been adequately explored. Here, we report a potent activator of ClpP with the therapeutic potential for pancreatic ductal adenocarcinoma (PDAC). We first validated that aberrant ClpP activation leads to growth arrest of PDAC cells and tumors. We then performed high-throughput screening and synthetic optimization, from which we identified ZG111, a potent activator of ClpP. ZG111 binds to ClpP and promotes the ClpP-mediated degradation of respiratory chain complexes. This degradation activates the JNK/c-Jun pathway, induces the endoplasmic reticulum stress response, and consequently causes the growth arrest of PDAC cells. ZG111 also produces inhibitory effects on tumor growth in cell line-derived and patient-derived xenograft mouse models. Altogether, our data demonstrate a promising therapeutic strategy for PDAC suppression through the chemical activation of ClpP. Graphical abstract: Highlights: An increase in ClpP protease activity suppresses PDAC tumorigenesis ClpP activator ZG111 aberrantly degrades respiratory chain complexes in PDAC cells ZG111 exerts antitumor effects on PDAC xenografted mice models Chemo-activation of ClpP represents a new therapeutic strategy against PDAC Abstract : ClpP activation disturbs mitochondrial proteome homeostasis and inhibits tumorigenesis. Wang et al. identify a potent ClpP activator ZG111 that degrades multiple respiratory chain complexes leading to dysregulated mitochondrial functions in PDAC cells. Their results illustrate ClpP activation as a promising therapeutic strategy against PDAC.